“Desempeño laboral y su incidencia dentro de las ventajas competitivas en las microempresas comerciales del Cantón la Maná, Provincia de Cotopaxi, año 2020.” - Marcillo Monsalve, Angel Omar (2021)
The role of micro-enterprises in business activity is fundamental, it has the potential for self-development, self-sufficiency and growth. The problem arose from the empirical management of microenterprises, lack of knowledge about the importance of quality job performance, the low rate of training, the academic level of the owners and the impact it generates on the competitive advantages of a business, the general objective of this project was to analyze the incidence of job performance on the competitive advantages of commercial microenterprises of La Maná canton; in order to fulfill this purpose, bibliographic and field research was used, among the methods the theoretical method was used: logical historical , deductive, synthetic analytical and empirical method: expert assessment, in addition descriptive and correctional research was used. It was taken as a base the population universe of 3,830 commercial micro enterprises and 1,668 collaborators of the urban sector, applying the calculation of the sampling by strata it was possible to obtain a sample of 150 proprietors and 143 collaborators to whom the surveys were applied whose instrument was the questionnaire that was validated. The most relevant findings indicated that there is a relationship of 0.628 according to the factors of work performance (work environment, organizational culture, incentives, work satisfaction, competence, education, knowledge and experience) and competitive advantage (leadership by cost, differentiation, concentration), demonstrating that work performance is of vital importance to obtain competitive advantages. It is concluded that work performance has an impact on competitive advantages. In view of the results found, the creation of generic competitive advantages was proposed in order to improve profitability conditions and reduce costs in strategic products.